The compromise of liberal environmentalism - Bernstein, Steven F. (Columbia international affairs online. Books., 2001)
The most significant shift in environmental governance over the last thirty years has been the convergence of environmental and liberal economic norms toward ""liberal environmentalism""?which predicates environmental protection on the promotion and maintenance of a liberal economic order. Steven Bernstein assesses the reasons for this historical shift, introduces a socio-evolutionary explanation for the selection of international norms, and considers the implications for our ability to address global environmental problems. The author maintains that the institutionalization of ""s